Analisis Kegiatan Market Day dalam Mengembangkan Kemampuan Sosial Anak Usia 5-6 Tahun di TK IT Bunayya 7 - Fadillah Aini Nasution; Nefi Darmayanti; Muhammad Basri (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
This study aims to analyze the implementation of Market Day activities in developing the social skills of children aged 5–6 years at TK IT Bunayya 7. The research focuses on planning, implementation, evaluation, and challenges faced by teachers during the process. A qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The subjects were 15 children from group B and their classroom teacher. The findings reveal that Market Day effectively fosters children’s social skills, including cooperation, communication, empathy, responsibility, and honesty. Through simple buying and selling activities, children learn to interact while practicing togetherness and Islamic values. Challenges identified include children’s inconsistent cooperation and teachers’ limited ability to manage the activities optimally. In conclusion, Market Day serves as a project-based learning method that provides meaningful, enjoyable, and contextual experiences to support the social development of early childhood.